Mixing, heat fluxes and heat content evolution of the Arctic Ocean mixed layer - A. Sirevaag; S. de la Rosa; I. Fer; M. Nicolaus; M. Tjernström; M. G. McPhee (Ocean Science, 2011)
A comprehensive measurement program was conducted during 16 days of a 3 week long ice pack drift, from 15 August to 1 September 2008 in the central Amundsen Basin, Arctic Ocean. The data, sampled as part of the Arctic Summer Cloud Ocean Study (ASCOS), included upper ocean stratification, mixing and heat transfer as well as transmittance solar radiation through the ice. The observations give insight into the evolution of the upper layers of the Arctic Ocean in the transition period from melting to freezing. The ocean mixed layer was found to be heated from above and, for summer conditions, the net heat flux through the ice accounted for 22 % of the observed change in mixed layer heat content. Heat was mixed downward within the mixed layer and a small, downward heat flux across the base of the mixed layer accounted for the accumulated heat in the upper cold halocline during the melting season. On average, the ocean mixed layer was cooled by an ocean heat flux at the ice/ocean interface (1.2 W m−2) and heated by solar radiation through the ice (−2.6 W m−2). An abrupt change in surface conditions halfway into the drift due to freezing and snowfall showed distinct signatures in the data set and allowed for inferences and comparisons to be made for cases of contrasting forcing conditions. Transmittance of solar radiation was reduced by 59 % in the latter period. From hydrographic observations obtained earlier in the melting season, in the same region, we infer a total fresh water equivalent of 3.3 m accumulated in the upper ocean, which together with the observed saltier winter mixed layer indicates a transition towards a more seasonal ice cover in the Arctic.